2019
DOI: 10.14738/assrj.611.7392
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of Exchange Rate Volatility On Real Estate Prices In Developing Economies, A Case Of Ghana

Abstract: This study aims to find out whether exchange rate volatility affects real estate domestic house prices in Ghana. To this end, a 32 years secondary data from World Development Indicators (WDI) and data from Real Estate Developers in Ghana are employed for the study. The study employs Autoregressive distributed lags (ARDL) bounds testing of cointegration t o test the null hypothesis that exchange rate volatility has n o impact on real estate housing prices. The study finds that real estate price is cointegrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Given that the appreciation of a currency makes domestic assets and commodities more expensive in the eyes of the international community, foreign investors are likely to reduce their demand for properties in South Africa. On another note, an appreciating exchange rate strengthens the value of local currency in relation to other currencies (Adu et al , 2019; Sumer and Özorhon, 2020). Finally, the study found that the inflation targeting framework, implemented in 2001, significantly reduced residential property prices.…”
Section: Results Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Given that the appreciation of a currency makes domestic assets and commodities more expensive in the eyes of the international community, foreign investors are likely to reduce their demand for properties in South Africa. On another note, an appreciating exchange rate strengthens the value of local currency in relation to other currencies (Adu et al , 2019; Sumer and Özorhon, 2020). Finally, the study found that the inflation targeting framework, implemented in 2001, significantly reduced residential property prices.…”
Section: Results Of the Studymentioning
confidence: 99%
“…The study has further noted that the exchange rate appreciation significantly reduces house prices. Adu et al (2019) also investigated the impact of exchange rate volatility in Ghana and found that the appreciation exchange rate significantly influences residential properties. The findings of Adu et al (2019) were also in line with the study’s findings regarding the consumer price index.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Ghana, Adu et al [18] examined the effects of exchange rate volatility on real estate prices in developing economies. This study aimed to find out whether exchange rate volatility affects real estate domestic house prices in Ghana.…”
Section: Survey Of Relevant Literaturementioning
confidence: 99%
“…There are several studies that have tried to examine the relationship between exchange rates and their fluctuations on real estate prices. For instance, Adu Jack et al (2019) using ARDL framework show that volatility in the exchange rate does not predict changes in real estate prices in Ghana. On the contrary, Benson et al (1999) realized that there is a positive and significant relationship between the exchange rate and housing prices in the Canadian economy, so that, a 10% rise in the exchange rate leads to a 7.7% rise in Bellingham home prices.…”
Section: Literature Reviewmentioning
confidence: 99%